A Phase I, Open‐Label, Single‐Dose Safety, Pharmacokinetic, and Tolerability Study of the Sumatriptan Iontophoretic Transdermal System in Adolescent Migraine Patients. Issue 8 (29th July 2016) - Gutman, Dikla; Hellriegel, Edward; Aycardi, Ernesto; Bigal, Marcelo E.; Kunta, Jeevan; Chitra, Rohini; Kansagra, Sujay; Kidron, Orna Srur; Knebel, Helena; Linder, Steven; Ma, Yuju; Pierce, Mark; et al.
Abstract : Objective: To evaluate the safety, tolerability, and pharmacokinetics of sumatriptan delivered by the iontophoretic transdermal system (TDS) in adolescent patients. Background: Since nausea can be a prominent and early symptom of migraine, nonoral treatment options are often required. Sumatriptan iontophoretic TDS is approved for the acute treatment of migraine in adults. The present study evaluates the pharmacokinetics of sumatriptan administered via the iontophoretic TDS in adolescents, contrasting the findings with historical data from adults. Design: Patients aged 12–17 years (inclusive) with acute migraine were treated with sumatriptan iontophoretic TDS for 4 hours. Blood samples for pharmacokinetic profiling of sumatriptan were obtained prior to dosing and at predetermined time points covering the 12 hours postonset of treatment. Key pharmacokinetic endpoints included C max (peak plasma drug concentration), t max (time to C max ), AUC0–∞ (area under the plasma concentration–time curve from time 0 to infinity), and t ½ (terminal elimination half‐life). Safety was evaluated by monitoring of adverse events in addition to laboratory and clinical assessments. Results: The sample consisted of 37 patients, and 36 were included in the PK evaluable population. C max, t max, AUC0–∞, and t ½ values were all similar between male and female patients and between younger (12–14 years) and older (15–17 years) adolescents. When compared with historical adult data, adolescent patients demonstrated similar systemic exposures to those observed in adults (mean C max 20.20 (±6.43) ng/mL in adolescents vs 21.89 (±6.15) ng/mL in adults; mean AUC0–∞ 98.1 (±28.1) ng·h/mL in adolescents vs 109.7 (±26.1) ng·h/mL in adults). All adverse events were mild or moderate, with application‐site paresthesia being the most common (32%). No clinically relevant changes in laboratory values, vital signs, or electrocardiogram findings were observed. Conclusions: The iontophoretic TDS produced mean systemic exposures to sumatriptan in younger and older adolescents, in line with what was seen in adult subjects. It was generally well tolerated.